Concomitant Intake of Quercetin with a Grain-Based Diet Acutely Lowers Postprandial Plasma Glucose and Lipid Concentrations in Pigs. (16th April 2014) - Wein, Silvia; Wolffram, Siegfried
Abstract : Treatment goals of diabetes mellitus type 2 (DMT2) include glycemic control and reduction of nonglycemic risk factors, for example, dyslipidemia. Quercetin, a plant-derived polyphenol, often discussed for possible antidiabetic effects, was investigated for acute postprandial glucose- and lipid-lowering effects in healthy growing pigs. Male pigs (n   =   16, body weight = BW 25–30 kg) were fed flavonoid-poor grain-based meals without (GBM) or with quercetin (GBMQ). In a first experiment, postprandial plasma concentrations of glucose, nonesterified fatty acids (NEFA), and triacylglycerols were analyzed in 8 pigs receiving 500 g of either GBM or GBMQ (10 mg/kg BW) in a cross-over design. Blood samples were collected before, and up to 5 h every 30 min, as well as 6 and 8 h after the feeding. In the second experiment, 2 h after ingestions of 1000 g of either GBM or GBMQ (50 mg/kg BW) animals were sacrificed; gastric content was collected and analyzed for dry matter content. Quercetin ingestion reduced postprandial glucose, NEFA, and TG concentration, but two hours after ingestion of the meal no effect on gastric emptying was observed. Our results point to inhibitory effects of quercetin on nutrient absorption, which appear not to be attributable to delayed gastric emptying.